Statistical MOSFET Parameter Extraction with Parameter Selection for Minimal Point Measurement - Marga Alisjahbana (Universitas Ahmad Dahlan, 2013)
A method to statistically extract MOSFET model parameters from a minimal number of transistor I(V) characteristic curve measurements, taken during fabrication process monitoring. It includes a sensitivity analysis of the model, test/measurement point selection, and a parameter extraction experiment on the process data. The actual extraction is based on a linear error model, the sensitivity of the MOSFET model with respect to the parameters, and Newton-Raphson iterations. Simulated results showed good accuracy of parameter extraction and I(V) curve fit for parameter deviations of up 20% from nominal values, including for a process shift of 10% from nominal.